2006
DOI: 10.1080/14622200600576610
|View full text |Cite
|
Sign up to set email alerts
|

Influences affecting adolescent smoking behavior in China

Abstract: This study examined multiple influences on the use of tobacco by adolescents in China. Using the theory of triadic influences as a guide, we selected interpersonal, attitudinal/cultural, and intrapersonal constructs from baseline data to predict adolescent smoking 1 year later. We used prospective data from middle and high school students (N = 11,583) and their parents from the China Seven Cities Study, a longitudinal study that is evaluating the effects of changing economic and social factors on health behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 59 publications
11
40
0
Order By: Relevance
“…The prevalence of past 1-month smoking, which includes both past 30-day and past 7-day smokers, was also similar to previous large-scale studies in the school students in China (Grenard et al, 2006;Johnson et al, 2006). Compared to other levels of smokers (never, ever and past 30-day), there was a significantly higher proportion of past 7-day smokers who had not made a firm commitment not to smoke in the next 12 months or cigarette offering from best friends, while there was no difference between past 30-day and ever smokers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The prevalence of past 1-month smoking, which includes both past 30-day and past 7-day smokers, was also similar to previous large-scale studies in the school students in China (Grenard et al, 2006;Johnson et al, 2006). Compared to other levels of smokers (never, ever and past 30-day), there was a significantly higher proportion of past 7-day smokers who had not made a firm commitment not to smoke in the next 12 months or cigarette offering from best friends, while there was no difference between past 30-day and ever smokers.…”
Section: Discussionsupporting
confidence: 87%
“…Third, in the study reported here, the past 30-day and past 7-day smokers sample sizes are relatively small. However, the prevalence and number of cigarettes smoked per day during the past 30 days in our sample was very similar to that found in other large-scale population studies of school students in China (Grenard et al, 2006;Johnson et al, 2006). Statistical significance on the decision task after controlling for demographic variables indicates that the effects are robust, and population representativeness of the sample, bolstered by inclusion of students from both major types of Chinese high schools, suggests that the findings are widely generalizable to Chinese youth.…”
Section: Limitationssupporting
confidence: 91%
“…These findings were replicated in a related co-occurring trial with a multiethnic cohort in California [21]. From a theoretical perspective, influences on smoking uptake and progression were found to be much the same in China as the USA, including perceptions of social norms, dispositional characteristics (depression and impulsivity), and causal attributions [22][23][24][25]. One difference was that parent, teacher, and other adult smoking practices played a more important role relative to peer smoking in the Chinese than in the US population [22].…”
Section: Adapting Western Theories To Chinese Conditions: the Case Ofmentioning
confidence: 73%
“…Other PR-TTAURC and CSCS studies have included an investigation of substance use among adolescent twin pairs in California and Qingdao to quantify the nature of environmental influences and how they interact with familial and genetic sources of variation in smoking-related behaviors [34]; an investigation of genetic factors underlying tobacco and alcohol use progression and their prevention [35]; a family study of cardiovascular risk factors in Qingdao [36], a study of the development and validation of a Chinese version of the Food Frequency Questionnaire for youth and adolescents [37]; an assessment of cognitive and neural mechanisms underlying tobacco and alcohol abuse [25][26][27]; and an assessment of tobacco use among rural Chinese children and their parents [38].…”
Section: Adapting Western Theories To Chinese Conditions: the Case Ofmentioning
confidence: 99%
“…Among Chinese adolescents, it is estimated that 33.3-47.8% of males and 12.8-24.3% of females have initiated smoking (i.e., have smoked at least once), and 15.0-18.30% of males and 1.7-4.0% of females are current smokers [29][30][31][32][33]. Despite substantial and documented tobacco control efforts in China, researchers have found only limited success in preventing or reducing tobacco use among adolescents [28,34].…”
Section: Cigarette Smoking In China: Prevalence and Existing Researchmentioning
confidence: 99%